Peran Asatizah Dalam Membentuk Karakter Santri di Muhammadiyah Boarding School (MBS) Aimas Kabupaten Sorong - Maulud Bauw; Muhammad Muzakki; Abdul Gani (Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the role of asatizah in shaping the character of students at Muhammadiyah Boarding School (MBS) Aimas, Sorong Regency. This study focuses on the influence of interaction and teaching methods of asatizah on the formation of students' character, which includes moral, spiritual, and social values. This study uses a qualitative method with a case study approach. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation. The results of the study indicate that asatizah have a very important role in shaping the character of students through several aspects, namely personal exemplary behavior, teaching applicable Islamic values, and habituating positive behavior in everyday life. The conclusion of this study is that the role of asatizah at MBS Aimas is very significant in shaping the character of students who have high integrity, responsibility, and social awareness. Therefore, it is recommended that MBS continue to increase the involvement of asatizah in the process of character education for students, by prioritizing aspects of exemplary behavior and more holistic guidance.